Costs of adopting radio frequency identification reader systems and tagging services in livestock auction markets - K. Bolte; Kevin C. Dhuyvetter; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2008)
Livestock industry initiatives such as the National Animal Identification System (NAIS), marketing alliances, and production verification programs are leading to increased use of electronic animal identification systems. Livestock markets are one place where animal movement and identification information can be recorded easily. Auction market facilities can differentiate themselves by offering electronic individual animal identification and tracking services to customers. However, facility modifications, installation, and operating equipment needed to record electronic animal identification information at the speed of commerce involves costs. The more animals that the radio frequency identification (RFID) reading technology would be used on, the lower the cost of investment per animal for the livestock market. Thus, auction markets will be reluctant to invest in RFID reading and recording equipment if there is little demand for the service by customers. This concern has likely increased with the NAIS becoming explicitly voluntary. Also, some market operators are concerned that producers will expect livestock markets to offer tagging services if RFID equipment is available for use. The investment required to adopt an electronic animal identification system and how this investment would affect a livestock market's business are also major concerns. This study examines the investments required for livestock markets to adopt RFID reader systems and tagging services.
Keywords: Cattlemen& #x27; s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; National Animal Identification System (NAIS); Radio frequency identification (RFID); Livestock auction markets